Exploring customers’ zone of tolerance for B2B professional service quality - Ho, A.; Sharma, Piyush; Hosie, P. (Emerald Group Publishing, 2015)
Purpose: This paper aims to extend the current research on zone of tolerance (ZOT) and its antecedents, to the context of business-to-business (B2B) professional services from both client and service firms’ perspectives, with a modified ZOT framework including five client and service firms attributes as antecedents of desired (DSL) and adequate (ASL) service levels. Prior research on zone of tolerance (ZOT) and its antecedents mostly focuses on business-to-consumer services and customers’ perspective. The authors address these gaps with a modified ZOT framework with five attributes of client and service firms as antecedents of customer expectations, namely, desired service level (DSL) and adequate service level (ASL), for business-to-business (B2B) professional services. Design/methodology/approach: A combination of qualitative (focus groups) and quantitative (online survey) research methods with managers of professional audit firms and their clients, using a reduced AUDITQUAL instrument with 39 items and seven dimensions.Findings: Professional firm size and fee premium have a positive effect on DSL; service tenure positively influences both DSL and ASL; client firm size has a negative effect on DSL; both client and service firm sizes positively moderate each other’s influence on the DSL; and DSL positively influences ASL. Research limitations/implications: The authors study a single B2B professional service (audit) in a single city (Hong Kong) from a single perspective (customers) that may limit the generalizability of the findings. Future research should validate the findings for other B2B professional services in diverse locations and also include service providers’ expectations and perceptions. Practical implications: Managers in professional service firms should understand the factors influencing different levels of expectations for their customers and develop suitable strategies (e.g. customer education and employee training) to manage these expectations more effectively. Originality/value: The authors extend current research on customer expectations and ZOT by identifying five unique attributes of professional service and client firms and testing their roles as antecedents of adequate and DSLs using AUDITQUAL instrument.